2020
DOI: 10.1038/s42256-020-0153-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning of circulating tumour cells

Abstract: Composition of training and validation sets. The original dataset used to train and validate our networks was obtained through the automated processing of 499 patient samples with ACCEPT and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 44 publications
0
53
0
Order By: Relevance
“…The F-score provides a measure of the overall performance of the model by considering the equal importance of precision and recall. As a comparison, in a recent study 47 , deep learning networks have shown the ability to unlock the hidden information in fluorescent images. The networks could classify fluorescent images of single cells including CTCs with a very high accuracy (96%).…”
Section: Resultsmentioning
confidence: 99%
“…The F-score provides a measure of the overall performance of the model by considering the equal importance of precision and recall. As a comparison, in a recent study 47 , deep learning networks have shown the ability to unlock the hidden information in fluorescent images. The networks could classify fluorescent images of single cells including CTCs with a very high accuracy (96%).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for the current analysis we restricted that part of our analysis to only 10% of the nucleated events which were randomly selected. Experience obtained with the deep learning based classification algorithm we developed showed very promising results and the new segmentation method also showed that it is often superior to the more traditional segmentation approach currently used in ACCEPT [ 22 ]. Thus, in the future, we would like to incorporate a semantic deep learning segmentation into the ACCEPT toolbox to automatically detect and classify CTC, tumor derived extra cellular vesicles, leukocytes, and other cell populations for which reagents are added.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of label‐free imaging, AI, and microfluidics is a subject of great interest in the scientific community to solve open biomedical questions 21,28‐31 . In particular, the authors of the present review strongly believe that such integration would represent a keystone for the identification of CTCs (Figure 1).…”
Section: Introductionmentioning
confidence: 87%
“…The latter refers to neural networks, that is, architectures that can operate directly on the input image (rather than its descriptors) and can learn, from a wide dataset, its most appropriate representation with several levels of abstraction 151‐154 . Deep learning approaches to image segmentation and classification have been demonstrated to be robust with a huge generalization power 15,19,20,28,29,154‐168 . Cell segmentation in microfluidic streams is obtainable using pretrained networks (eg, Mask R‐CNN and Faster R‐CNN) 151,152,167 .…”
Section: Deep Learning‐assisted Imaging For Cell Identificationmentioning
confidence: 99%
See 1 more Smart Citation